2023
DOI: 10.1002/ange.202217581
|View full text |Cite
|
Sign up to set email alerts
|

New Oxyhalide Solid Electrolytes with High Lithium Ionic Conductivity >10 mS cm−1for All‐Solid‐State Batteries

Abstract: All-solid-state batteries (ASSBs) with inorganic solid electrolytes (SEs) have attracted significant interest as next-generation energy storage. Halides such as Li 3 YCl 6 are promising candidates for SE because they combine high oxidation stability and deformability. However, the ionic conductivities of halide SEs are not as high as those of other SEs, especially sulfides. Here, we discover new lithium-metal-oxy-halide materials, LiMOCl 4 (M = Nb, Ta). They exhibit extremely high ionic conductivities of 10.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…All-solid-state lithium batteries (ASSLBs) have received research interest due to the several key advantages over current liquid lithium batteries, including improved safety, better mechanical/thermal stability, and the potential to achieve the requirement of energy/power density. This brings a significant focus on the development of solid-state electrolytes (SSEs) as the SSEs directly influence the performance of the whole battery. , For example, different kinds of inorganic SSEs, such as polymer-, oxide-, sulfide-, and halide-based SSEs, have been extensively investigated. …”
Section: Introductionmentioning
confidence: 99%
“…All-solid-state lithium batteries (ASSLBs) have received research interest due to the several key advantages over current liquid lithium batteries, including improved safety, better mechanical/thermal stability, and the potential to achieve the requirement of energy/power density. This brings a significant focus on the development of solid-state electrolytes (SSEs) as the SSEs directly influence the performance of the whole battery. , For example, different kinds of inorganic SSEs, such as polymer-, oxide-, sulfide-, and halide-based SSEs, have been extensively investigated. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, attention should be paid to the challenges posed by the Li/SE interface, such as the formation of a stable and low-resistance interface, which is not yet achieved by LYBC as SE, although recent studies have demonstrated excellent stability with Li metal using either a new LaCl 3 -based halide SE or a fluorinated halide SE. Moreover, opting for a more highly conductive SE may significantly improve rate capabilities and high loading performance. In that regard, one might consider the use of the recently explored lithium–metal-oxyhalide SE family that have demonstrated ionic conductivities exceeding 10 mS/cm while potentially retaining the halide SE ductility that we believe necessary for low-pressure operation. This encourages further exploration and research into new halide-based SE materials.…”
mentioning
confidence: 99%
“…Since then, an upsurge of interest has been brought to ternary halides, accruing from their high resistance to oxidation when they are in contact with high voltage cathodes. Several ternary halides Li 3 YCl 6 , Li 3 ErCl 6 , Li 3 InCl 6 , , Li x ScCl 3+ x , , Li 2 ZrCl 6 , , 0.5LiCl·SmCl 3 , LiMCl 6 (M = Ta, Nb) and their aliovalent substituted variants, Li 3– x M 1– x Zr x Cl 6 (M = Y, Er, In, Ho, Lu), Li 3– x Yb 1– x M x Cl 6 (M = Hf 4+ , Zr 4+ ), , LiMOCl 4 (M = Nb, Ta), ZrO 2 (-LiCl)-Li 2 ZrCl 6 , Li 2+ x ‑ y ZrCl 6‑ x ‑ y O x , x Li 2 O-MCl y (M = Ta, Hf), have been (re)­investigated. Aliovalent substitution of M 3+ with a tetravalent cation led to an increase in the conductivity by several orders of magnitude. High conductivities up to several mS cm –1 at room temperature have been achieved in several compositions, , , , yet the underlying ion conduction mechanism remains elusive.…”
mentioning
confidence: 99%
“…Several ternary halides Li 3 YCl 6 , Li 3 ErCl 6 , Li 3 InCl 6 , , Li x ScCl 3+ x , , Li 2 ZrCl 6 , , 0.5LiCl·SmCl 3 , LiMCl 6 (M = Ta, Nb) and their aliovalent substituted variants, Li 3– x M 1– x Zr x Cl 6 (M = Y, Er, In, Ho, Lu), Li 3– x Yb 1– x M x Cl 6 (M = Hf 4+ , Zr 4+ ), , LiMOCl 4 (M = Nb, Ta), ZrO 2 (-LiCl)-Li 2 ZrCl 6 , Li 2+ x ‑ y ZrCl 6‑ x ‑ y O x , x Li 2 O-MCl y (M = Ta, Hf), have been (re)­investigated. Aliovalent substitution of M 3+ with a tetravalent cation led to an increase in the conductivity by several orders of magnitude. High conductivities up to several mS cm –1 at room temperature have been achieved in several compositions, , , , yet the underlying ion conduction mechanism remains elusive. Previous studies on the factors affecting the ion transport of lithium-conducting halides focus on the nonlithium cation disorder, ,, polyhedral distortion, , stacking faults, etc., while the influence of Li/vacancy concentration on the ion transport mechanism and ion transport property has not been elucidated in detail.…”
mentioning
confidence: 99%